H-function with complex parameters I: existence - Fadhel A. Al-Musallam; Vu Kim Tuan (International Journal of Mathematics and Mathematical Sciences)
An H-function with complex parameters is defined by a Mellin-Barnes type integral. Necessary and sufficient conditions under which the integral defining the H-function converges absolutely are established. Some properties, special cases, and an application to integral transforms are given.